β-blockers and statins: exploring the potential off-label applications in breast, colorectal, prostate, and lung cancers - Braga, Pedro Gabriel Senger; Vieira, Janaína da Silva; Gurgel, Aline Rachel Bezerra; Brum, Patricia Chakur (Frontiers in Pharmacology, 2024)
Despite advances in cancer treatment, current cancer incidence and prevalence still demand multimodal treatments to enhance survival and clinical outcomes. Drugs used in cardiology, such as β-blockers and statins have gained attention for their potential roles in oncology. This study focuses on their possible complementary use in solid tumors, including breast, colorectal, lung, and prostate cancers. The involvement of the autonomic nervous system in promoting tumor growth can be disrupted by β-blockers, potentially hindering cancer progression. Statins, known for their pleiotropic effects, may also inhibit cancer growth by reducing cholesterol availability, a key factor in cell proliferation. We will provide an update on the impact of these therapies on cancer treatment and surveillance, discuss the underlying mechanisms, and explore their effects on the heart, contributing to the growing field of cardio-oncology.